Penggunaan media Stick Figure berbasis permainan papan edukatif untuk meningkatkan keterampilan menulis aksara Jawa nglegena peserta didik kelas III sekolah dasar - Wasis, Tri; Sadiman, Sadiman; Daryanto, Joko (Universitas Sebelas Maret, 2019)
The study aims to improve the writing skills of javanese alphabet nglegena through the use of media Stick Figure based on educational board games in class III students of Selodoko 2 elementary school, Ampel Sub-district, Boyolali Districk, in academic year 2018/2019. The form of this research is Classroom Action Research conducted in two cycles. The subjects of this study were third grade teachers and students. Data collection techniques in this study used interview, observation, documentation, and test techniques. Test the validity of the data using content validity, source triangulation and technical triangulation. The data analysis technique used interactive analysis according to Miles and Huberman. Increase in the average score of the four aspects from the pre-action with the score of 2,09 increasing up to 2,48 in the first cycle then increase again in the cycle 2 with a score of 3,26. The average aspect influences the value of aspects of writing skills Javanese alphabet nglegena. Therefore, it can be concluded that the use of media Stick Figure based on educational board games can improve writing skills in Javanese alphabet nglegena in class III students of Selodoko 2 elementary school, Ampel Sub-district, Boyolali District.Keywords: media Stick Figure based on educational board games, Javanese alphabet nglegena writing skill, elementary school